Pengaturan Transparansi Beneficial Ownership di Sektor Jasa Keuangan dalam Rangka Pencegahan dan Pemberantasan TPPU - Novariza, Novariza (PAMPAS: Journal of Criminal Law, 2021)
This article discusses two main issues, first how the beneficial ownership concept stipulated in the FATF recommendation is adopted in the financial services sector of anti-money laundering regulation. Second, how beneficial ownership transparency regulation can assist efforts in preventing and eradicating money laundering offenses. The research will look at the legal substance or doctrinal aspects of beneficial ownership reporting regulations in the anti-money laundering legal framework and program, then juxtaposed with Presidential Decree 13/2018 and its compliance with the standards set out in the recommendations of the FATF, considering that Indonesia actually adopted the FATF recommendation. The conclusion of this article is first, that the concept of beneficial ownership in the anti-money laundering regime in Indonesia has fully adopted the provisions and standards of the FATF recommendations, but only within the regulatory framework at the regulatory level, whereas at the laws and presidential regulations level regulate only part of it. Second, identification and transparency of beneficial ownership is a key factor in the prevention and eradication of money laundering offenses, both in relation to supervision and law enforcement in the context of recovering assets from proceeds of crime. Â  ABSTRAK Artikel ini membahas, pertama bagaimana konsep beneficial ownership (pemilik manfaat) yang diatur dalam rekomendasi FATF diadopsi dalam regulasi anti pencucian uang di sektor jasa keuangan di Indonesia. Kedua bagaimana pengaturan transparansi beneficial ownership membantu upaya pencegahan, pemberantasan TPPU di sektor jasa keuangan. Metode yang dipergunakan dalam artikel adalah yuridis normatif. Hasil dari artikel ini pertama, konsep beneficial ownership dalam rezim anti pencucian uang di Indonesia mengadopsi penuh ketentuan dan standar dari rekomendasi FATF namun hanya dalam kerangka regulasi tingkat peraturan regulator. Sementara level undang-undang, peraturan presiden, baru mengatur sebagian ketentuan FATF terkait beneficial ownership korporasi. Kedua, identifikasi dan transparansi beneficial ownership sebagai kunci Pencegahan dan pemberantasan TPPU, baik kaitannya dengan pengawasan maupun penegakan hukum dalam rangka pemulihan aset hasil tindak pidana.